2016
DOI: 10.1371/journal.pone.0162226
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cognitive Bias Modification Interventions for Substance Addictions: A Meta-Analysis

Abstract: Background and AimsCognitive bias modification (CBM) interventions, presumably targeting automatic processes, are considered particularly promising for addictions. We conducted a meta-analysis examining randomized controlled trials (RCTs) of CBM for substance addiction outcomes.MethodsStudies were identified through systematic searches in bibliographical databases. We included RCTs of CBM interventions, alone or in combination with other treatments, for any type of addiction. We examined trial risk of bias, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
190
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 26 publications
5
190
0
Order By: Relevance
“…Modification of these automatic biases could be achieved with tasks such as the visual-probe task (which involves the repeated pairing of probes with neutral stimulus) (6); the approach/avoidance task (which involves presenting the salient stimulus in a push-away format) (7); and lastly cognitive bias modification for interpretation (which involves training individuals to disambiguate ambiguous scenarios in a positive way) (8). Prior reviews have synthesised the evidence for cognitive bias modification (Cristea et (9)'s review, 25 trials involving participants with alcohol and tobacco disorder were identified, and they found bias modification to be effective for attentional and approach biases, with an effect size of 0.60 (Hedge G). Jones et al (2017) reviewed meta-analyses and reported that cognitive bias modification was effective for anxiety disorders, with effect sizes ranging from 0.13 to 0.74 (10).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of these automatic biases could be achieved with tasks such as the visual-probe task (which involves the repeated pairing of probes with neutral stimulus) (6); the approach/avoidance task (which involves presenting the salient stimulus in a push-away format) (7); and lastly cognitive bias modification for interpretation (which involves training individuals to disambiguate ambiguous scenarios in a positive way) (8). Prior reviews have synthesised the evidence for cognitive bias modification (Cristea et (9)'s review, 25 trials involving participants with alcohol and tobacco disorder were identified, and they found bias modification to be effective for attentional and approach biases, with an effect size of 0.60 (Hedge G). Jones et al (2017) reviewed meta-analyses and reported that cognitive bias modification was effective for anxiety disorders, with effect sizes ranging from 0.13 to 0.74 (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported no effects of bias modification on other addiction outcomes or on craving (9). A commentary published (10) in response to this meta-analysis (9) highlighted that a mixture of clinical and non-clinical studies have been included in the evidence synthesis and if only clinical studies were considered, the qualitative synthesis demonstrates that there was a significant effect of bias modification. For anxiety and depressive disorders, there remains to be small effect sizes (Hedges g of 0.37) for the bias modification (Cristea et al, 2015), based on a prior evaluation of 49 trials (11).…”
Section: Introductionmentioning
confidence: 99%
“…Cristea et al (2016) (4) in their meta-analysis considered the effect size of attentional bias modification on cognitive biases, as well as on addiction-related outcomes and cravings. The metaanalysis included 25 randomised trials involving individuals with either alcohol use or tobacco use disorders.…”
Section: Introductionmentioning
confidence: 99%